THE INFLUENCE OF STUDENTSâ SELF EFFICACY TOWARD THEIR READING ACHIEVEMENT AT SMA SRIJAYA NEGARA PALEMBANG - Yuliani, Sri (STKIP Muhammadiyah Pringsewu, 2016)
The formulation of the problem was âIs there any significant influence of studentsâself efficacy toward their English reading achievement?â. Therefore, the objective ofthis study was to find out whether or not : there is a significant influence of studentsâsself efficacy toward their English reading achievement. To conduct this studydescriptive quantitative was used. The population of the study consisted of 242students of SMA Srijaya Negara Palembang in the academic year of 2014/2015. Thewriter chose 2 classes of tenth grade students which consisted of 68 students. Thesample was selected by using convinience sampling. The data were collected by usingquestionnaire and test. The data were analyzed by using correlational (spearman rho)and regression analysis. The result showed that there was weak correlation betweenstudentsâ self efficacy toward their English reading achievement (r=.399). Theinfluence of studentsâ self efficacy was 0.219 or 21.9 % to the studentsâ Englishreading achievement. From the F-test, it can be seen that the F-obtained was 18.472with the significant level p < 0.05 was higher than the value of F-table (F-table = 3.98). Since the F-obtained was higher than F-table, the alternative hypothesis (Ha) wasaccepted and the null hypothesis (H o ) was rejected. So it could be concluded that therewas a significant influence of studentsâ self efficacy toward their English readingachievement at SMA Srijaya Negara Palembang.Keywords : Influence, Self Efficacy, and English Reading Achievement